FAKTOR - FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN ASAM URAT PADA LANSIA (45 – 70 TAHUN) - Ridhyalla Afnuhazi (HUMAN CARE JOURNAL, 2019)
Indonesian is the 4th largest country in the world whose in habitants suffer from gout. In Indonesian, it is estimated that uric acid occur in 840 people every 100,000 people. Disease of gout is one of the degenerative disease. One of the signs of the disease gout is the increase in the levels of uric acid in the blood (hiperurisemia). Factors related to the incidence of hiperurisemia is sex, IMT, intake carbohydrate sand intake purin. Purin intake is a risk factor most strongly associated with the incidence of hiperurisemia. This study used a cross-sectional research design cross method i.e. research to study the dynamics of the correlation between two variables. Research carried out in the Puskesmas Kebun Sikolos in August 2016. The population in this study amounts to 100 people. Sampling techniques in "accidental sampling", with a sample of as many as 20 people. Data processing is carried out using the SPSS program with computerized analysis univariate and bivariat, statistical tests used was chi-square. The results of the univariate analysis showed that (65%) of respondents-sex women, (55%) of respondents experiencing obesity and (55%) of the respondents did not suffer from hypertension. Bivariat analysis p value = 0.019 means there is a relationship between the sex with uric acid, and p value = 0.025 means there is a connection between obesity with uric acid, and p value = 0.337 which means there is no relationship between hypertension with the occurrence of uric acid. Thus the factors associated with the incidence of gout in the elderly is gender and obesity. So from that recommended that health workers improve outreach program again about the factors associated with the incidence of gout in the elderly.